Experimental study and numerical models assessment of turbulent mixed convection heat transfer in a vertical open cavity. (April 2017) - Yang, Guang; Huang, Yiye; Wu, Jingyi; Zhang, Liangjun; Chen, Guozhen; Lv, Rongrong; Cai, Aifeng
Abstract: Flow and heat transfer in a vertical open cavity with turbulent mixed convection is investigated experimentally and numerically. The internal size of the cavity is 1 m × 1 m × 1.2 m, with liquid nitrogen as the cold source and mica electronic heating plates as the heat source of the experiments. The velocity and temperature fields are obtained by hot-wire anemometry, particle image velocimetry and local temperature sensors for 4.6 × 10 4  ≤ Re ≤ 5.9 × 10 4 and Gr ≤ 1.8 × 10 13 . The secondary upward flow was found to occur near the heated walls. Three two-equation RANS turbulence models, RNG k-ε model, L-B Low Re k-ε model and SST k-ω model, are used in the numerical simulation with the same boundary conditions as experiments. Through comparison with experimental data, Low Re k-ε model performs overall the best in the accuracy in solving mixed convection problems in large-scale vertical cavities with strong buoyancy force. Highlights: Experiments was designed for turbulent mixed convection in a vertical open cavity. Results were obtained by HWA and PIV for high Grashof numbers of Gr = 1.8 × 10 13 . The buoyancy induced secondary upward flow was found to occur near the heated walls. Numerical simulations with different two-equation turbulence models were conducted. Low Re k-ε model performs the best in mixed convection in large scale cavities with high Gr.